Moral Leadership and Climate Change Policy: The Role of the World Conservation Union. Issue 1 (2nd January 2020) - Taylor, Prue; Brown, Don; Burdon, Peter
ABSTRACT: The importance and urgency of using ethical principles in the creation and content of climate change policy is well recognised. This article closely examines the World Conservation Union's (IUCN) engagement in ethical elements of international climate policy for abatement. The primary finding is the use of narrow framing around 'nature based solutions'. The IUCNs' own policy references to ethical principles such as fairness and justice are not adequately applied to the content of policy or to its critique. Recommendations are made on how the IUCN (and NGOs generally) could enhance its ethical engagement to act consistently with the claim of moral leadership.